Indonesia's Foreign Policy Post-Reform in the United Nations Security Council - Muhammad Zuhal Lukman (Ilomata International Journal of Social Science, 2023)
Indonesia has a national interest in carrying out the constitutional mandate in terms of maintaining active involvement to affirm that independence is the right of all nations and colonialism is contrary to the arguments of humanity and justice. Therefore, through United Nations Security Council, Indonesia rejects all forms of colonialism, including issues between Israel and Palestine. This research focuses on Indonesia's foreign policy and its capacity as a Non-Permanent Member of the UN Security Council. The method used is a qualitative method with a literature study that is validated through an explicit confirmation process at the Ministry of Foreign Affairs, while the analytical framework used is a comparative foreign policy perspective to map the factors that influence the process of making Indonesian foreign policy in different terms of office, that is president Susilo Bambang Yudhoyono 2007-2008 and Joko Widodo 2019-2020. The findings of this study indicate that consideration of enacting Indonesia's foreign policy on Palestine is a sustainable policy with the roots of the constitutional mandate and Indonesia's commitments in the past, that’s why almost no major changes can be found even though they have gone through the presidential transition process. Palestine also can be has a vital position for Indonesia considering that Palestine is the only conflicting country that has always existed in a formal discussion of Indonesian state documents. The difference can be found in how each reign reacts to external factors such as the invasion or blockade that Israel has done.